The Amazing Adventure of Equiano - Vayssieres, Jean-Jacques (Literamed Publications (Nig) Ltd, 1998)
The story of Equiano is arguably the best known slave narrative ever published.The book traces the journey of a young African boy of the Ibo tribe,from his capture by Africans and then by whites when he was Ten Years Old.
Keywords: Juvenile literature- Non-Fiction